Instability of Crop-yields and Product Prices in Saurashtra Region of Gujarat - Kuchhadiya, D B; Shiyani, R L; Thumar, B L (Annals of Arid Zone, 2016)
The trend in area. production and productivity of crops and product price variability in Saurashtra (Gujarat) was examined. Compound growth rates of productivity were significantly positive for all the crops except maize. Instability in crop yields was the highest for sorghum and castor. There was high co-variance between product prices, and the instability of product price was the highest for sugarcane and groundnut. Creation of irrigation facilities and setting up of grain reserves and fodder banks are suggested for the development of the area.